Peculiarities of The Orientational State of Liquid-Crystal Completely Aromatic Thermotropic Copolymer - Ryzhov, V.A. (Journal of Research Updates in Polymer Science, 2017)
Polarization far-IR spectroscopy has been used to carry out a comparative study of the spectra of granules and fibers of completely aromatic thermotropic liquid-crystal copolymer Vectra A950. The analysis of terahertz polarization IR spectra Vectra A950 showed that in contrast to the mid-IR, dichroic ratio of the absorption bands in the spectra of fibers and granules, substantially different. It is shown that the difference between the value and the orientation order parameter in the samples is determined by and correlated with the intensity of the local dynamics of polymer chains, such as the librational mobility of phenylene and naphthalene rings of the copolymer mesogens. The results suggest the possibility carrying out an independent evaluation of the spectroscopic parameters reflecting the properties of intermolecular interactions in oriented the liquid-crystalline polymers for their low-frequency spectra.